Water Consumption by a Young Apple Orchard of Intensive Type - YESSENGELDIYEVA, Perizat N.; MUSSABEKOV, Kydyraly K.; NURABAYEV, Daulen M.; ZHATKANBAYEVA, Ainur O.; TUMENBAYEVA, Nagima T. (Journal of Environmental Management and Tourism; Vol 11 No 5 (2020): JEMT Volume XI Issue 5(45) Fall 2020, 2020)
Water consumption consists of the moisture reserves of the soil used by plants, atmospheric precipitation of the growing season, capillary recharge of groundwater (if their bedding is close to the surface) and irrigation water. Water consumption in the apple orchard during the growing season was compensated by precipitation, irrigation rate, and the use of soil moisture from the root layer. Along with the total water consumption of the apple orchard, water balance calculations were carried out on the distribution of water consumption by vegetation months at 70% of the HB humidification regime and moisture saturation depths according to years of research. The thickness of the moistened layer is from 0.40 to 0.60 m. Water balance calculations to determine the total water consumption of the apple orchard were carried out for four years of research, characterized by different heat and moisture supply, both for the whole year and for the growing months.